Effect of green tea and sodium ascorbate on the shear bond strength of orthodontic brackets bonded on bleached enamel: An in-vitro study - Sakshi Tiwari; Garadappagari Dharmadeep; K. Sadashiva Shetty; Deepthi Shiri (Journal of Oral Biology and Craniofacial Research)
Objective: The primary objective was to assess and compare the shear bond strength of orthodontic brackets bonded on bleached enamel with and without using an anti-oxidizing agent.The secondary objective was to compare the shear bond strength of brackets between the groups with anti-oxidant application along with immediate bonding and that of delayed bonding without any anti-oxidant treatment, on bleached teeth. Materials & methods: 75 premolars were collected and thereafter randomly distributed into the 5 groups. Group 1 to 4 had undergone bleaching with 10% carbamide peroxide and group 5 was control. Group 1 was bonded immediately after bleaching while bonding was delayed in group 4 for a period of 1 week. Groups 2 and 3 received the anti-oxidant treatment with 10% sodium ascorbate gel and 10% green tea gel respectively. Hounsfield universal testing machine was used for testing the shear bond strength. Results: For group 1, the shear bond strength was significantly lower (mean 4.9 MPa) than group 5 (mean 12.5 MPa). The significant differences were observed on comparing the shear bond strength of antioxidant-treated and delayed bonding groups with control (p < 0.05). Mean shear bond strength in groups 2, 3 and 4 were 7.5 MPa, 9.6 MPa and 5.8 MPa respectively. Conclusion: The bond strength of brackets reduces immediately after the bleaching procedure. The bond strength can be reversed either by delaying the bonding for a period of 1 week or by using the anti-oxidizing agents but it is not up to the level of unbleached enamel.